Analysis of Communication Media Factors and Organizational Change Development on Integration between Business Cooperation Actors of Fakfak Regency's Superior Products - Elin Lismaya; Sri Rahayu; Suryono Suryono; Sundjoto Sundjoto (RTTM, 2023)
Communication media and organizational change development are expected to be the key to growing the integrity of business actors in Fakfak district's superior products in building a cooperation network. The purpose of the research is to determine the level of ability to utilize communication media and the expertise of business people in Fakfak district's superior products to move organizations in order to build business cooperation. The research began in May – December 2023. Descriptive research method with a combination of quantitative and qualitative analysis approaches. Data was obtained through a direct survey of respondents who had been deliberately determined. The data obtained are given a weight value based on the assessment indicators obtained from the results of the preliminary research. The validity and reliability of the data were tested gradually and in a structured manner using the triangulation and role sharing approaches. The results of the study are presented in the form of a spider web diagram equipped with an illustration of the shift share gap value, a root cause analysis diagram with a combination of weighting techniques, pearson correlation analysis, and a regression equation model obtained from the SPSS statistical device version 2.3.